Sarcopterygian Fishes from the Early Triassic of Svalbard: The Fish Niveau and Grippia Bonebed - Larsen, Rudi Bjerknes (2023)
The sarcopterygian fishes are today represented by the two groups Actinistia (coelacanths) and Dipnoi (lungfish). Both groups survived the end-Permian mass extinction (EPME), after which the coelacanths rapidly achieved their greatest taxonomic diversity. On Svalbard, the coelacanths and lungfishes are represented within two Early Triassic horizons: the Fish Niveau (Smithian) and the Grippia Bonebed (Spathian). The Fish Niveau contains large amounts of actinistian material preserved in concretions, whilst the material from the Grippia Bonebed is represented by largely disarticulated actinistian elements and dipnoan tooth plates. An actinistian presence in the Grippia Bonebed is identified from isolated basisphenoids and several morphotypes of quadrate bones. The dipnoans are represented by weathered tooth plates. Several more ambiguous elements from the bonebed are tentatively assigned to the Sarcopterygii. The Fish Niveau material in this study is represented by actinistian material mainly from the jaw and hyobranchial apparatus. A large actinistian gular plate from the Fish Niveau belonged to an individual estimated to about 2.2 meters in total length, the largest Triassic coelacanth known so far. Likewise, large quadrate bones from the Grippia Bonebed also indicate large-bodied coelacanths. All these specimens likely belonged to more basal coelacanths outside of the more derived clade Latimerioidei, which contain most of the largest coelacanths known. Both horizons exhibit several forms of coelacanths of various sizes, indicating that the ecosystems were trophically complex. Dipnoan tooth plates only appear infrequently. Based on the scarcity, weathering, and well-attested transition of dipnoans from marine to freshwater habitats, these specimens were likely transported onto the marine shelf from a terrestrial freshwater source.